2021
DOI: 10.9734/jpri/2021/v33i60b34848
|View full text |Cite
|
Sign up to set email alerts
|

Gingival Recession among the Patients Wearing Fixed Braces Visiting Dental College of Larkana

Abstract: Aim: To evaluate gingival recession among the patients wearing fixed braces visiting dental college of Larkana. Study Design: Descriptive Cross-Sectional Place and Duration of Study: Department of Orthodontics, Bibi Aseefa Dental College (BADC) Larkana December 2018 to February 2020. Methodology: This study was carried out at Bibi Aseefa Dental College Larkana. The patients were recruited with consecutive sampling technique. The gingival recession was evaluated clinically using Miller`s class… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Consistently, Akkaya M 17 reported that the average age of the young adult group is 22.36±2.82 years. On the other hand, in a national study by Shar MK 18 , the mean age of the patients was 21.03±4.684 years; males were 23% and females were 77%. Khan KH 19 reported that the mean age of the patients was 21.3±3.45 years, and of the total 50 patients, 23 (46%) were males and 27 (54%) were females.…”
Section: Discussionmentioning
confidence: 91%
“…Consistently, Akkaya M 17 reported that the average age of the young adult group is 22.36±2.82 years. On the other hand, in a national study by Shar MK 18 , the mean age of the patients was 21.03±4.684 years; males were 23% and females were 77%. Khan KH 19 reported that the mean age of the patients was 21.3±3.45 years, and of the total 50 patients, 23 (46%) were males and 27 (54%) were females.…”
Section: Discussionmentioning
confidence: 91%